(untitled) (American Journal of Islam and Society, 2010)
Refreshingly candid and at times contradictory, not to mention multidisciplinary and entirely provocative, this book’s alternative and polished graphic and design immediately places it outside mainstream architecture texts on contemporary mosque design. Although specifically focused on the contemporary design of mosques in the Netherlands, its broader and more general understandings are easily grasped through its grounded arguments. Many of the chapters also contextualize issues of mosque design in that country within the larger scope of mosque design in the West. Each of the ten chapters is written by a different author: architects, architectural historians, philosophers, politicians, and other experts. Titled with a provocative question, the introductory short commentary ties together what may at first seem like disparate interpretations of the contemporary mosque’s role and design ...